Teaching about frogs in Grade 7: a case study on integrating indigenous knowledge into the science curriculum. - Minter, Jean Elizabeth (My University, 2005)
Constructivism and worldview theory were translated into the design of a series of science lessons for Grade 7 learners. Indigenous knowledge about frogs, elicited from the local community, was incorporated into the lessons together with frog myths from other cultures, in order to introduce the curricular topics of conservation and biodiversity. The lessons then focussed on pollution of our natural environments and the loss of biodiversity as evidenced by declining frog populations. The lessons were implemented by the researcher and the participants’ activities were assessed using rubrics. Participants’ attitudes towards frogs were assessed using pre- and post-test questionnaires. Qualitative analysis of the data revealed that experiences and learning had taken place amongst the participants, and had resulted in a more positive attitude towards frogs. Participants had also developed a better understanding and appreciation of biodiversity and the need for its conservation. Lessons learnt from the research were that information on indigenous knowledge about frogs was not available in the literature and that no guidance was given to teachers regarding the incorporation of indigenous knowledge into the South African Science curriculum, and that some aspects of the assessment had been subjective and needed to be improved. Nevertheless, the researcher has shown that by introducing indigenous knowledge in a series of science lessons, using constructivist principles, and acknowledging the existence of differing worldviews, it is possible to expose learners to positive and effective learning experiences that foster the development of an appreciation of the importance of conservation and the need to maintain biodiversity.
Thesis (M.Sc.) (Education) --University of Limpopo, 2005.
Keywords: Not available